RFID Application in the Supply Chain - Vatovec Krmac, Evelin (Promet - Traffic&Transportation, 2006)
This paper analyses the possibilities and ways of utilizingRFID as a tool for more effective supply and logistics chainmanagement. It focuses on RFID technology used within andacross logistics processes and it looks to RFID as one of thepossibilities for automating logistics processes. The benefitsand implications of RFID technology implementation in thesupply chain are illumined.